Removal of as and cd ions from aqueous solution using biosorption technique - W. N., Wan Fauzi; Farah Shahirah, Mohd Fairuz; Nurasmat, Mohd Shukri; Nur Fatien, Muhamad Salleh; Wan Nazwanie, Wan Abdullah; Norshahidatul Akmar, Mohd Shohaimi; Ahmad Zamani, Ab Halim; Nor Hakimin, Abdullah (Institute of Physics, 2022)
Arsenic (As) and cadmium (Cd) are listed as heavy metals that have contaminated the environment, especially water supplies. Therefore, the goal of this study was to remove heavy metals, particularly As and Cd metal ions, from aqueous solutions by utilizing natural waste adsorbents and at the same time, help in the reduction of waste products. This study was designed to use low-cost and more widely available adsorbents material such as coconut husk and banana peel to remove As and Cd ions in an aqueous solution. The adsorption method was utilized to reduce and remove the As and Cd ions, and their concentrations in an aqueous solution were then determined by Atomic Absorption Spectroscopy (AAS). Various parameters such as types of adsorbents (banana peel and coconut husk), adsorbent dosages (0.1-0.3g), contact time (30-70 minutes), and temperature (25-45°C) were used to carry out the removal process. The FTIR analysis revealed that certain heavy metals were more likely to bind to these adsorbents due to the presence of important functional groups such as hydroxyl (-OH) and carbonyl (C=O). From this study, the optimum removal conditions were 0.1 g dose of adsorbent along with 70 minutes of contact time at a reaction temperature of 25°C. The results revealed that banana peel removed 0.948 mg/L of Cd ions and 0.148 mg/L of As ions from the aqueous solution, suggesting that it was more efficient at removing heavy metals than coconut husk. Meanwhile, Cd ions have a higher affinity (93.9% to 99.9% removal) than As ions (8.3% to 22.2% removal) to adsorb onto the active sites of banana peel and be removed from an aqueous solution. In conclusion, the adsorption technique using natural waste adsorbents can be applied to remove the As and Cd ions from the aqueous solutions. The reduction of these heavy metals' concentration by adsorbents can also help to preserve the quality of water sources under the permissible limit set by WHO.